Training and Development Policy, Corporate Governance, and Firm Performance - Rayenda Khresna Brahmana; Ritzky Karina Brahmana; Theresa Char Fei Ho (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2018)
This research investigates the role of corporate governance as a moderator between firms’ performance and their Training and Development Policy (TDP). Research data were taken from the US, Brazil, Russia, India, China and Indonesia from 2007 to 2013. This research found that the TDP is important for enhancing firm performance. Also, the role of the training and development policy impacted each firm’s performance differently, according to the level of corporate governance of that firm. The moderating effect of corporate governance reveals that better governance of a firm may have an influence on its TDP policy, which would lead to better firm performance. Overall, the results are consistent with the conjecture that corporate governance influences the firm’s performance and training and development policy, suggesting that the training and development policy’s success depends on the corporate governance level of the firm. Hence, this research contributes to two big theories: the knowledge transfer theory and the human capital theory, where the research findings show a confirmation of the two theories application in this research context.